Mom, are we Shi'a? Neg(oti)ating Sectarian Identity in Everyday Life in Post-2011 Bahrain - Fibiger, Thomas (The review of faith & international affairs, 2020)
Based on ethnographic fieldwork experiences in Bahrain in 2017 and 2018, but also drawing on long-term work with this country since 2003, I suggest in this article that questions of sectarianization and de-sectarianization are important, but cannot be definitely answered. While many Bahrainis identify strongly as either Sunni or Shi'a Muslims, at the same time they highlight that this should not be all that defines them, and that de-, cross- or non-sectarian relations are both possible and important, also and not least in the wake of the ill-fated uprising in 2011.